Book Review: What is Mission? Theological Explorations - Desi Natalia (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
J. Andrew Kirk’s writing deals with three parts. Parts I lays the groundwork for how the church should carry out its mission. This is closely related to apologetics. Classically, tradition refers to the accumulated wisdom of the Christian community throughout the ages, which is inherited and passed on from one generation to another. Part II contemporary issues in mission contains the use of the words “evangelism” or “Evangelism” prominently in Church thought in the last one hundred and fifty years. The main emphasis in declaring the good news is conveying an extremely important piece of information that states it is true and relevant. Humans are immersed in culture. Part III this mission in action has the assumption that going and being in the world is a form of mission, the Church must see herself as a people on the move. It is a community that “looks to” and “purposes.” To separate mission from life in the community is to abstain from the resources that make mission possible in the way of Christ. Political reality is very complicated. Thoughts will change and mission tools will change to suit the new situation. There might be alternative combinations to unify the various aspects of the mission.